PEDAGOGICAL CONDITIONS IN THE FORMATION OF SKILLS OF ANALYTICAL ANALYSIS OF STUDENTS IN THE FIELD OF BIOINFORMATICS (Intent Research Scientific Journal, 2023)
In this research work, students studying in the field of information technology use tasks aimed at the development of personality, reflecting the structure and content of the skills of analytical analysis of the appropriate formation of analytical skills, directing independent work of students mainly in research activities in the process of studying bioinformational technologies, relying on the method of implemented projects using bioinformational technologies, the focus of the educator and students was defined and justified such conditions as the implementation of the interaction of the person standing.